I am Heath Ledger - Buitenhuis, Adrian; Murray, Derik; Lawless, Shaun (Dazzler Media, 2017)
"I Am Heath Ledger" is a documentary which focuses on the life of the late Australian actor. Through interviews with Ledger's family, friends, co-workers, and loves, the movie explores Ledger's humble beginnings in Australia, where he lead a pretty normal life, save for the fact that he clearly liked being a performer. After earning the lead in the short-lived Australian-lensed television show "Roar", Ledger moved to America to try his luck in Hollywood. It didn't take long for him to find success in "10 Things I Hate About You". He could have easily pursued roles in other teen-focused movies, but instead, he sought parts in a diverse set of dramas, including "Monster's Ball" and "The Four Feathers". Ledger really showed his willingness to separate himself from his peers by starring in "Brokeback Mountain", a role which earned him an Oscar nod. However, Ledger would undergo his most severe transformation for his role at "The Joker" in "The Dark Knight", for which he finally won an Academy Award. Unfortunately, that honor came posthumously, as Ledger died on January, 22, 2008 from a drug overdose. [www.dvdsleuth.com]
Keywords: DVD-Video